Asymmetrical Blood Flow in the Temporal Lobe in the Charles Bonnet Syndrome: Serial Neuroimaging Study - N. Adachi; M. Nagayama; K. Anami; K. Arima; H. Matsuda (Behavioural Neurology)
Clinical features and results of neuroimagings of an 86 year old woman with the Charles Bonnet syndrome are reported. She had become completely blind bilaterally due to cataracts and glaucoma. Shortly after an operation for cataracts, she developed visual hallucinations which lasted for 22 years. She had no deterioration of intelligence. Computed tomography (CT) and magnetic resonance imaging (MRI) showed moderate generalized atrophy, particularly of the temporal lobes. A serial single photon emission computed tomography (SPECT) study during visual hallucinations demonstrated hyperperfusion in the left temporal region and the basal ganglia and hypoperfusion in the right temporal region. These findings suggest that asymmetrical blood flow, particularly in the temporal regions, may be correlated with visual hallucination in the Charles Bonnet syndrome.